Assessing the performance of innovation platforms in crop-livestock agro-ecosystems in the Volta basin - Ayantunde, Augustine A.; Swaans, Cornelis P.M.; Some, Hubert W.; Pali, Pamela N. (Academic Journals, 2016)
To enhance integrated rainwater management in crop-livestock systems in the Volta basin of Burkina Faso, innovation platforms (IP) comprising of multiple stakeholders were established in the districts of Koubri and Ouahigouya. Quarterly IP meetings were organized to collectively identify and prioritize constraints and opportunities, and to design and implement strategies to address them. IP represents an example of putting the agricultural innovations systems’ perspective into practice. Several studies have evaluated the performance of IPs, but these are often based on external (mainly qualitative) assessments during mid-term and/or end evaluation. In this study we are interested in how key processes develop over time and how this is perceived by participants themselves, since this determines the participation and commitment of stakeholders and hence the success of the IP. To ensure adequate documentation of IP processes and activities, several monitoring and evaluation tools were developed. This paper focuses on the assessment of the IP performance in terms of consistency of participation across meetings and stakeholder groups, relevance of identified issues, information exchange, conflict resolution, participation in decision making, facilitation, and perceived benefits. For all the indicators used to assess the IP, the mean scores tended to increase with the lifespan of the IPs. This reaffirms that the IP is perceived as valuable by its members as a way to enhance agricultural development. At the same time though an IP is not a “quick-win”, but takes time to mature for it to become fully functional and achieve desired outcomes.